Ail expression in Yersinia enterocolitica is affected by oxygen tension. - Pederson, K J (1995)
We investigated several environmental factors for their abilities to regulate ail gene expression and found that ail transcript levels are regulated by oxygen tension. Bacteria growing under anaerobiosis at 37 degrees C repress ail mRNA and Ail expression, resulting in a loss of Ail-mediated serum resistance and cell invasion.